SAURON Observations of Disks in Early-Type Galaxies - Bureau, M; Copin, Y; Verolme, E; Zeeuw, P; Bacon, R; Emsellem, E; Davies, R; Kuntschner, H; Carollo, C; Miller, B; Monnet, G; Peletier, R (2000)
We briefly describe the SAURON project, aimed at determining the intrinsic shape and internal dynamics of spheroids. We focus here on the ability of SAURON to identify gaseous and stellar disks and to measure their morphology and kinematics. We illustrate some of our results with complete maps of NGC3377, NGC3623, and NGC4365.